(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2017)
It is important to note that the human arts in different cultures and civilizations are an aesthetic product that reveals the transformation of the intellectual dimensions and the various mechanisms of expression to the surrounding knowledge data, which resulted in diversity in the way the composition of the artistic product in order to show it in aesthetic form. Therefore, the selected research (transformed into the products of Qajari ceramics) included four chapters: The first chapter was devoted to explaining the problem of the research, its importance and the need for it, as well as determining the objective: (detection of the variable in the products of Qajari ceramics). The second included the theoretical framework, which contained three topics: the first topic / the first axis: the conceptual transformation. The first topic / The second axis: Mechanisms of transformation in art. The second topic / The relationship of transformation to creativity and theories. The third topic: The transformation in Qajari art. The research included the third chapter (research procedures), in which the methodology (descriptive approach) and the method of analyzing the content of the models (the sample of the research) were determined by (3) models and intentionally. The fourth and final chapter contains the results. • The transformations in the Khajar scenes are divided into two main parts: A - Religious transformations: appeared in most of the ceramic products of Qajarip, especially inspired by the Quranic and historical stories, including the phenomenon of the child and a simulated voice of the personalities of the people of the house and prophets (peace be upon them). As in Model (1, 2) B - worldly transformations: and appeared in the models that dealt with the stories of the fictional and portrayal of the kings of the kings and portray the scenes naked women and the physical / sensory in those scenes. As in the models (3) This chapter also contains conclusions, recommendations and proposals. And ended up documenting documented Arab and foreign sources.